Frequency domain analysis on acoustic emission signal in bone tissues - Muhammad Hafiz, Ramli (2012)
The purpose of this study is to study acoustic emission signal in bone tissues. The objectives of this research are to determine acoustic emission (AE) signal in different types of bone tissue; hard and soft bone’s tissue and to observe the trend of acoustic emission signal for penetration during pedicle screw fixation procedure. It also to propose a method to help medical practitioner in penetration process during pedicle screw fixation procedure using acoustic emission technique. Generally, the medical practitioner had a hard time while doing the pedicle screw fixation procedure when it involved with cervical spine. The cervical spine is the most complicated articular system in the body because the anatomy of the region which are close to spinal cord. This study would help to monitor the penetration process. For this study, goat vertebras were use as specimen. During pedicle screw fixation procedure, pedicle probe is used to penetrate the specimen and sensor captured the AE signal and recorded data with help of AEWin Software. Using FFT analysis the result show dominant frequency in compact bone is high compare to spongy bone. AE signal also can be measure when pedicle probe penetrated through the interface of the bone tissues during the pedicle screw fixation procedure. In conclusion, AE technique can use for monitoring acoustic emission signal produced by specimen in pedicle screw fixation procedure.